2011
DOI: 10.1002/rcm.4945
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the flow of bacterially derived13C and15N through soil faunal feeding channels

Abstract: The soil food web has been referred to as a 'black box', a 'poor man's tropical rainforest' and an 'enigma', due to its opacity, diversity and the limited insight into feeding specificity. Here we investigate the flow of C and N through the soil food web as a way to gain understanding of the feeding interactions occurring. A bacterium, Pseudomonas lurida, was introduced to soil cores from two different habitats, a grassland and a woodland with the same soil type, enriched to 99 atom% in (13)C and (15)N, to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 59 publications
(132 reference statements)
0
54
0
Order By: Relevance
“…The grassland site had received no inorganic-N fertiliser for over 30 years although it had been grazed annually by cattle and the floral assemblage was predominantly grass species. The willow woodland was planted approximately 25 years ago and although coppiced regularly in the first 5 years after planting, it has not been coppiced or disturbed in the last 10 years; the botanical composition of the cores taken consisted of under-canopy woodland forbs (for full site descriptions, see Crotty et al [13] and also Table 1). Ten intact soil cores (10-cm diameter, 10-cm deep) were collected in April 2010, from each site.…”
Section: Site Descriptions and Samplingmentioning
confidence: 99%
See 3 more Smart Citations
“…The grassland site had received no inorganic-N fertiliser for over 30 years although it had been grazed annually by cattle and the floral assemblage was predominantly grass species. The willow woodland was planted approximately 25 years ago and although coppiced regularly in the first 5 years after planting, it has not been coppiced or disturbed in the last 10 years; the botanical composition of the cores taken consisted of under-canopy woodland forbs (for full site descriptions, see Crotty et al [13] and also Table 1). Ten intact soil cores (10-cm diameter, 10-cm deep) were collected in April 2010, from each site.…”
Section: Site Descriptions and Samplingmentioning
confidence: 99%
“…Gas samples were analysed for 13 CO 2 only, using a trace gas analyser (TGII, PDZ-Europa, Crewe, UK) linked to a mass spectrometer (20/20 PDZ-Europa, Crewe, UK). The isotope abundance in the plant, soil, headspace gas and invertebrate samples are expressed as atom% excess (APE) 13 C or 15 N and calculated as Eqs. 1 and 2.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Remén et al (2010) and Crowther et al (2005Crowther et al ( , 2010 carried out soil microcosms with only one oribatid species and with a single micorrhiza or saprotrophic fungi species and the decrease of fungus biomass consumed by mites was monitored. Crotty et al (2010) introduced bacteria enriched to 99 atom% in 13 C and 15 N to soil cores in laboratory and traced the flow of isotopes through the food web. They found that some of the oribatid mite species were enriched both in 13 Anderson (1978) demonstrated in a microcosm experiment that Nothrus silvestris and Hermanniella granulata Nicolet, 1855 compete with each other because the presence of both species in mini ecosystems affected their feeding and distribution over microcosm layers.…”
Section: Objectives Of Microcosm Studiesmentioning
confidence: 99%